(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2021)
Providing clean and affordable drinking water is one of the modern-times challenges. The world’s growing population causes water scarcity, and pollutants contaminate whatever water sources are left. Nanotechnology has provided innovative solutions for water purification. This chapter reviews nanotechnology-enabled water-treatment processes, showing how they transform our water supply and wastewater treatment.